Bioactive compounds in blackberry fruits under the conditions of Central Russia - М. A. Мakarkina; О. A. Vetrova; L. A. Gruner; B. B. Kornilov (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Blackberry is becoming increasingly popular in Russia for its rapid early-fruiting, high self-fertility and late flowering, contributing to longer consumption of fresh berries, a source of antioxidant compounds. There is a need to study the biochemical composition of blackberries.Materials and methods. Fruits of 25 blackberry cultivars and hybrid seedlings from the Institute of Fruit Crop Breeding (VNIISPK) were analyzed for the contents of catechins, leucoanthocyanins, anthocyanins, and total phenolic compounds using the photometric method, and the content of ascorbic acid using the titrimetric method. Statistical data processing was carried out using the methods of variation and correlation analyses.Results. Bioactive compounds (BAC) accumulating in blackberry fruits were studied: ascorbic acid, catechins, leukoanthocyanins, anthocyanins, and total phenolics, with medium and significant variability of the studied indicators (V > 10%). Among the genotypes, 73% accumulated more than 20.0 mg/100 g of ascorbic acid in fruits. All genotypes were identified as sources of anthocyanins. About 50% of the accessions accumulated catechins in fruits above the average level. Leucoanthocyanins were stored in blackberry fruits in slightly larger amounts than catechins. In 10 accessions the level of phenolics was higher than 1000.0 mg/100 g.Conclusion. Genotypes with high BAC content were identified. Correlation coefficients were obtained: they indicate the presence of an medium degree of rectilinear relationship between the content of ascorbic acid and anthocyanin compounds, ascorbic acid and total phenolics. Cvs. ‘Black Satin’, ‘Cacanska Bestrna’, ‘Chester’, ‘Natchez’ and ‘Triple Crown’, plus hybrid seedlings LN-14, LN-1 and LN-7, were identified according to a set of indicators (ascorbic acid and phenolics) and recommended for breeding to improve the quality of blackberry fruits.